Governance and development - reciprocal influence, increasing tensions : a case study into Barbados' Services Development Strategy - Marshall, Don D. (ECCB BasseterreKN, 1999)
Seeks to interrogate the current preference in the Caribbean fo offshore services or 'international business' as a strategy, to militate aganist the harsh effects of 'globalisation' . Gives Barbados significant address not only because it is mooted as a replicable model for others in the region to emulate, but it has gone furthest to invoke nationalism as a defence against the excess of the internationala neoliberal agenda.